Microstructure construction design and damping properties of polyurethane microporous elastomer modified by suspension chain extender via end-controlling oriented synthesis. (27th March 2023) - Tang, Xiaohao; Guo, Xin; Gong, Li; Meng, Xiangze; Xiu, Zhilun; Xin, Haobo; Liu, Li; Zhang, Baogang
Abstract: Broadening the damping temperature range of viscoelastic microporous polyurethane elastomers (MPUE) is a challenge to break the limits of practical applications in damping field. Based on the molecular reaction kinetics and the molecular structure design of MPUE, different molecular weight suspension chain extenders were synthesized from polyethylene glycol monomethyl ether (MPEG), isophorone diisocyanate (IPDI) and 2-amino-1, 3-propanediol via end-controlling oriented synthesis. The effect of molecular weight and dosages of suspension chain extenders on the damping property of MPUE was studied. It was demonstrated that strong intermolecular hydrogen bonds can be formed between MPUE molecules due to the carbamate groups and urea groups of the suspension chain extenders. The transformations of various motion modes of the suspended chain were driven by the existence of a large number of ether bonds, which can reduce the micro-phase separation degree in the material matrix, resulting in higher kinetic friction between molecular chains. The damping properties of the material were significantly improved, presenting a maximum increase of 62.3% in the effective damping temperature domain, and a maximum increase of 34.0% in the peak loss factor (tan δ), which was attributed to the synergistic compound effect of multiple motion modes. This high damping MPUE has great application prospects in the fields of acoustic noise reduction and household appliances damping. Graphical abstract: Image 1 Highlights: Different molecular weight suspension chain extenders were synthesized by end-controlling oriented synthesis. The suspension chain allowed the formation of stronger intermolecular hydrogen bonds within the system. The microphase separation of the material is significantly reduced. The synergistic compounding effect of multiple modes leads to a significant improvement of the damping properties of the material.